Mouse Models of Nonalcoholic Steatohepatitis: Head-to-Head Comparison of Dietary Models and Impact on Inflammation and Animal Welfare. (13th July 2020) - Kroh, Andreas; Ivanova, Vanina; Drescher, Hannah; Andruszkow, Julia; Longerich, Thomas; Nolting, Jochen; Eickhoff, Roman; Heise, D.; Rheinwalt, Karl P.; Neumann, Ulf P.; Ulmer, Florian T.
Abstract : A variety of dietary nonalcoholic steatohepatitis (NASH) mouse models are available, and choosing the appropriate mouse model is one of the most important steps in the design of NASH studies. In addition to the histopathological and metabolic findings of NASH, a sufficient mouse model should guarantee a robust clinical status and good animal welfare. Three different NASH diets, a high-fat diet (HFD60), a western diet (WD), and a cafeteria diet (CAFD), were fed for 12 or 16 weeks. Metabolic assessment was conducted at baseline and before scheduled sacrifice, and liver inflammation was analyzed via fluorescence-associated cell sorting and histopathological examination. Clinical health conditions were scored weekly to assess the impact on animal welfare. The HFD60 and WD were identified as suitable NASH mouse models without a significant strain on animal welfare. Furthermore, the progression of inflammation and liver fibrosis was associated with a decreased proportion of CD3 + NK1.1 + cells. The WD represents a model of advanced-stage NASH, and the HFD60 is a strong model of nonalcoholic fatty liver disease (NAFLD) and metabolic syndrome. However, the CAFD should not be considered a NASH model.